TAFSIR SAINTIFIK THANTHAWI JAUHARI ATAS SURAH AL-FATIHAH - Fathor Rahman (STAI ALHIKMAH Jakarta, 2016)
Abstract Understanding to al-Fatihah surah-as an overview of Qur’an (Qur’anniyah verses) will find the whole of meaning when combined with reading about phenomena of the universe (kauniyyah verses). Because, the truth of Qur’an is stronger when confronted with the signs of Allah that spread in universe, similarly the affirmation of God in (Fusilat Surah: 53). Among the mufassir who are pretty good figure combines between Qur’anniyah Verses and kauniyyah verses are Thanthawi Jauhari on his interpretation book titled al-Jawahir fi Tafsir al-Qur’an al-Karim. This reason is the main reason to writer to do research deeply to Thanthawi Jauhari’s interpretation about al-Fatihah Surah on his interpretation book titled al-Jawahir fi tafsir al- Quran al-Karim. To focus on the research above, there are some essential problems which need to be found the answer on this research, namely; how interpretation of Thanthawi Jauhari about al-Fatihah Surah on his interpretation book titled al-jawahir fi Tafsir al-Quran al-Karim? and how the methodology of Thanthawi Jauhari on interpreting al-fatihah Surah. To answer that 2 questions, the writer uses descriptive- analytical approach, that try to give information and description clearly, systematically, objectively, and analytically about the interpretation of Thanthawi Jauhari of al-Fatihah surah on his interpretation book al-jawahir fi Tafsir al-Quran al-Karim included the methodology used. Kata Kunci: Tafsir, scientific, Surah al-fatihah Abstrak Pemahaman terhadap surat al-Fatihah – sebagai sebuah ikhtisar al-Qur’an (ayat-ayat Qur’āniyyah) – akan menemukan keutuhan maknanya apabila dipadukan dengan pembacaan terhadap fenomena alam semesta (ayat-ayat kauniyyah). Sebab, kebenaran al-Qur’an semakin terkukuhkan ketika dihadapkan kepada tanda-tanda kebesaran Allah yang terhampar di alam semesta. Demikian penegasan Allah dalam Q.S. Fuṣṣilat: 53. Diantarasosokmufasiryangcukupbagusmemadukanantaraayat- ayat Qur’āniyyah dengan ayat-ayat kauniyyah adalah Thanthawi Jauhari dalam kitab tafsirnya yang berjudul al-Jawāhir fī Tafsīr al-Qur’ān al-Karīm. Alasan inilah yang melatarbelakangi penulis untuk melakukan kajian lebih mendalam terhadap penafsiran Thanthawi Jauhari tentang surat al-Fatihah dalam kitab tafsirnya yang berjudul al-Jawāhir fī Tafsīr al-Qur’ān al-Karīm. Untuk menfokuskan kajian di atas, maka ada beberapa masalah pokok yang perlu ditemukan jawabannya dalam penelitian ini, yaitu: Bagaimanapenafsiran Thanthawi Jauhari tentang surat al- Fatihah dalam kitab tafsirnya yang berjudul al-Jawāhir fī Tafsīr al-Qur’ān al-Karīm ? Dan bagaimana metodologi Thanthawi Jauhari dalam menafsirkan surat al-Fatihah? Untuk menjawab dua pertanyaan tersebut, penulis menggunakan pendekatan deskriptif-analitis, yaitu berupaya memberikan keterangandangambaranyangsejelas-jelasnyasecarasistematis, obyektif, dan analitis tentang penafsiran Thanthawi Jauhari terhadap surat al-Fatihah dalam kitabnya al-Jawāhir fī Tafsīr al- Qur’ān al-Karīm beserta metodologi yang digunakannya. Kata Kunci: Tafsir, saintifik, Surah al-fatihah